What Works in Reducing the Risk of Recidivism in the Maltese Context? An Evaluation of a Reintegrative Community-Based Rehabilitation Program. - Tabone, Yanika; Sammut Henwood, Kevin (International Journal of Offender Therapy & Comparative Criminology, 2026)
This quantitative study assessed the efficacy of a community-based rehabilitation program implemented by RISe Foundation Malta, designed to facilitate the reintegration of incarcerated individuals within the last 12 months before release. The intervention, grounded in the Risk-Need-Responsivity (RNR) Model and the Good Lives Model (GLM), aimed to mitigate recidivism by addressing dynamic risk factors associated with criminality. A retrospective analysis of 40 archived case files of program completers was conducted, extracting relevant data from reports to evaluate pre- and post-intervention changes. The data were analyzed using McNemar's test in SPSS. Results revealed a significant reduction in the presence of dynamic risk factors—such as issues related to social and psychological needs—following program completion. These findings provide empirical support for the application of the RNR and GLM models in community-based rehabilitation, demonstrating their potential to effectively reduce the propensity for reoffending. Plain language summary: What Helps Prevent Reoffending in Malta? A Study of a Community-Based Program This study looked at the effectiveness of a rehabilitation program run by the RISe Foundation Malta, aimed at helping people who were about to be released from prison reintegrate into the community. The program focused on reducing the factors that are linked to criminal behavior. It was based on two well-known models: the Risk-Need-Responsivity Model and the Good Lives Model. The researchers reviewed 40 case files of people who completed the program and compared their situation before and after participation. The results showed a significant decrease in the risk factors for reoffending, suggesting that the program helped reduce the likelihood of these individuals committing crimes again. This supports the use of these models in rehabilitation programs to help prevent recidivism.